Kebertahanan Kesenian Basing Komunitas Kajang Dalam Tantangan Global - Samidi Samidi; Sarkawi B. Husain (Institut Seni Indonesia Denpasar, 2023)
This article describes traditional arts dealing with global challenges. Globalization that makes it easy for everyone to express entertainment arts is a serious threat to Basing's traditional arts. The slowness of adaptation and regeneration further distances Basing's art from everyday life. The people of Kajang are trying to maintain it, but recently they have faced many obstacles. The mechanism that is still maintained is the relation of traditional art to the ritual of prayer for death. The purpose of this paper is to explain the relationship between traditioal art and rituals for the death and the constraints to inherit the art. This research used qualitative data that collected and analyzed based on village monograph, participant observations, and interviews. The observation is carried out during the Basing art performance at the death prayer ritual. The interviews were conducted on several people which proportionally representing social roles, including traditional community leaders, village government bureaucrats, teachers, youth art activists, village elders, and artists. The research found that restriction to the customary areas is only able to control people's behavior based on customary values and norms, but is not able to force residents to develop the Basing arts. However, the inheritance of arts faces obstacles because the people of Kajang are not able to carry out cadre of artists as successors and reinforcers of the existence of Basing art.